Changes in organic carbon, structure and nematode density in boreal soils following conversion from grassland to cropland - Hyväluoma, Jari; Keskinen, Riikka; Niemi, Petri; Salminen, Janne; Kinnunen, Sami; Miettinen, Arttu; Kaseva, Janne; Soinne, Helena (Elsevier, 2026)
Grasslands are known to be beneficial for increasing carbon stocks in soils as well as enhancing a range of essential soil ecosystem functions. Conversion of grassland to cropland can lead to loss of these benefits. The purpose of this study was to consider how the soil properties are altered after such land-use change in the boreal climate. Our study setup consisted of three fields which had been under extensive grassland management from 10 to over 30 years. Part of each field was ploughed and taken to cereal production and the rest was left as grassland. Carbon dioxide (CO2) fluxes from soil were measured during two growing seasons, and after the two years, the soil carbon stock, structure, and nematode densities were determined from both ploughed and undisturbed soils. Our results showed a practically and statistically significant land use change-induced reduction in soil carbon stock after two years. A significant reduction in the particulate organic carbon fraction was detected after the change. However, neither soil structural measures determined with X-ray tomography nor nematode density showed systematic alteration after the land-use change. Our results suggest that slow accumulation of carbon in soil leading to elevated carbon stocks can be easily lost if the favourable soil management ceases, which calls for long-term commitment to carbon conservation practices if lasting impacts are strived for.
Keywords: land-use change; soil management; grassland; soil structure; nematode abundance; particulate organic carbon; mineral-associated organic carbon